Financial Feasibility Analysis of XYZ Company Market Expansion Plan to Kalimantan - Tsabita, Dinara; Kitri, Mandra Lazuardi (Journal Integration of Management Studies, 2024)
XYZ Company, a B2B manufacturer of Songkok in Gresik, East Java, plans to expand its market by establishing a new distribution warehouse in Banjarmasin, Kalimantan. This strategy aims to leverage the growing demand for Songkok in Kalimantan, which has a significant Muslim population. The primary goal of this study is to evaluate the financial feasibility of purchasing versus renting the new warehouse for this investment plan. The financial feasibility analysis was conducted in multiple stages. Pro forma financial statements were constructed for both scenarios, incorporating historical data of the company's financial statements, industry benchmarks, and growth assumptions from management interviews. Free Cash Flow to the Firm (FCFF) and terminal cash flows were calculated using the Weighted Average Cost of Capital (WACC). Capital budgeting techniques were then used to evaluate financial feasibility, including Net Present Value (NPV), Internal Rate of Return (IRR), and Discounted Payback Period. Risk assessment was performed through sensitivity analysis and Monte Carlo simulation. Results indicate that the renting scenario, with an initial investment of IDR 242 million, has a higher NPV and IRR than the purchase scenario, which requires an initial investment of IDR 944 million. The renting scenario also offers a faster-discounted payback period of 2 years and one month, making it more feasible. Risk assessment shows moderate risk, with an 83% probability of achieving a positive NPV. The financial feasibility analysis recommends renting the new warehouse in Banjarmasin. This option provides a quicker payback period, higher NPV and IRR, and positive risk assessment results. Investing in this project will enhance XYZ Company's market presence in Kalimantan, cater to the growing demand for Songkok, and achieve sustainable growth and profitability.